Inflammatory bowel disease and pancreatic cancer: a Scandinavian register‐based cohort study 1969‐2017. Issue 1 (15th May 2020) - Everhov, Åsa H.; Erichsen, Rune; Sachs, Michael C.; Pedersen, Lars; Halfvarson, Jonas; Askling, Johan; Ekbom, Anders; Ludvigsson, Jonas F.; Sørensen, Henrik Toft; Olén, Ola
Summary: Background: Patients with inflammatory bowel disease (IBD) have an increased risk of cancer. Aim: To assess the risk of pancreatic cancer in IBD compared to the general population. Methods: Patients with incident IBD 1969‐2017 were identified in Danish and Swedish National Patient Registers and through biopsy data, and were matched to IBD‐free reference individuals by sex, age, place of residence and year of IBD diagnosis. We linked data to Cancer and Causes of Death Registers and examined the absolute and relative risks of pancreatic cancer and pancreatic cancer death. Results: Among 161 926 patients followed for 2 000 951 person years, 442 (0.27%) were diagnosed with pancreatic cancer compared to 3386 (0.21%) of the 1 599 024 reference individuals. The 20‐year cumulative incidence was 0.34% (95% confidence interval 0.30‐0.38) vs 0.29% (0.28‐0.30). The incidence rate was 22.1 (20.1‐24.2)/100 000 person years in the patients (excluding the first year of follow‐up: 20.8 [18.8‐23.0]), and 16.6 (16.0‐17.2) in the reference individuals. The hazard ratio (HR) for pancreatic cancer was increased overall: 1.43 (1.30‐1.58), in subtypes (Crohn's disease: 1.44 [1.18‐1.74]; ulcerative colitis: 1.35 [1.19‐1.53]; IBD unclassified: 1.99 [1.50‐2.64]) and especially in IBD patients with primary sclerosing cholangitis: 7.55 (4.94‐11.5). Patients and reference individuals with pancreatic cancer did not differ in cancer stage ( P  = 0.17) or pancreatic cancer mortality (HR 1.07 [0.95‐1.21]). Conclusions: Patients with IBD had an excess risk of pancreatic cancer, in particular patients with primary sclerosing cholangitis. However, the cumulative incidence difference after 20 years was small: 0.05%, that is, one extra pancreatic cancer per 2000 IBD patients.